Ultra-precision Machinability and Properties of Electroless-nickel - Pramanik, Alokesh; Basak, A. (Trans Tech Publications Inc, 2013)
Electroless-nickel (EN) and very few other materials are suitable for ultra-precision machining. This material exhibits excellent properties such as hardness, corrosion resistance which are essential for molding die. This paper discusses the properties of EN and links with the ultra-precision machinability of this material. It is found that chip formation processes changes with the cutting condition. Phosphorus content and heat treatments significantly affect the machinability of EN in terms of tool wear, machining force and surface finish.